Participation of the Monoaminergic System in the Antidepressant-Like Actions of Estrogens: A Review in Preclinical Studies - López-Rubalcava, Carolina; Vega-Rivera, Nelly Maritza; Páez-Martínez, Nayeli; Estrada-Camarena, Erika (IntechOpen, 2012)
None